Curvularia lunata: A fungus for possible berberine transformation - SARIYAR AKBULUT, BERNA (My University, 2022)
Abstract: The prevalence of multidrug-resistant microorganisms results in an urgent need for the development of new antimicrobial agents or new treatment strategies. In this sense, plants serve different alternatives. Berberine, a plantderived compound, is one of the alkaloids known to display antimicrobial activity against several types of microorganisms, while its being a substrate of various efflux pumps causes a decrease in its efficacy. Biotransformation makes it possible to obtain novel or more effective compounds with only minor structural modifications using enzyme systems. In this study, biotransformation of berberine by Curvularia lunata was examined. The working concentration of berberine was determined by observing the microbial growth on agar plates. The concentration of residual berberine in the media was analyzed by HPLC. In addition, laccase and beta-glucosidase enzyme activities were followed for their possible roles during the biotransformation of berberine. The results show that at the end of 14 days, C. lunata consumed 99% and 87% of berberine with the initial concentrations of 0.35 mg/mL and 0.5 mg/mL, respectively. Enzyme activities were not affected significantly. Since the concentration of berberine decreased, the biotransformation of berberine by C. lunata could be mentioned. Monitoring of biotransformation products plays a crucial role in discovering novel antimicrobial compounds and new valuable molecules.
Keywords: Biotransformation; Berberine; Curvularia lunata; Antimicrobial resistance